INTERNAL FACTOR EFFECTS IN FORMING THE SUCCESS OF SMALL BUSINESSES - GS, achmad daengs (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2020)
ABSTRACT. The objective of this study to analyses the effects of entrepreneurial competency, marketing capability, financial resources, technology usage, knowledge sharing to business success on Small-Micro Enterprises built by Industrial and Trade Agency of Surabaya. This study employs explanatory study type. Data collection technique that used is Structural Equation Model (SEM) with Smart Partial Least Square (PLS) aided tools. The upshot of this research shows that : (1) Entrepreneurial Competency has significant effect to Business Success, (2) Marketing Capability has significant effect to Business Success ; (3) Financial Resources has not significant to Business Success; (4) Technology Usage has significant effect to Business Success; (5) Knowledge sharing has significant effect to Business Success.Â Keywords : Entrepreneurial Competency, Marketing Capability, Financial Resources, Technology Usage, Knowledge Sharing